AMPK-mediated crosstalk of heteroglycan-induced reactive species and autophagic cascade in RAW 264.7 cells. Issue 49 (30th May 2015) - Devi, K. Sanjana P.; Das, Joyjyoti; Kumari, Kalpana; Singh, Prashant; Behera, Birendra; Maiti, T. K.
<x xml:space="preserve">Abstract</x> AMPK mediates the crosstalk among heteroglycan-induced autophagy and reactive species in RAW 264.7 cells.